2016
DOI: 10.1177/1367006916637288
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive consequences of trilingualism

Abstract: Aims and Objectives The objectives of the present research were to examine the cognitive consequences of trilingualism and explain them relative to the cognitive consequences of bilingualism. Approach A comparison of cognitive abilities in trilinguals and bilinguals was conducted. In addition, we proposed a cognitive plasticity framework to account for cognitive differences and similarities between trilinguals and bilinguals. Data and Analysis Three aspects of cognition were analyzed: (1) cognitive reserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 92 publications
(153 reference statements)
4
27
0
Order By: Relevance
“…The advantage in the non-linguistic switching tasks yielded by interpreting instead of translation experiences at an early stage of interpreting experience suggests that high-processing demands may be critical to improving cognitive control, which may be able to explain the inconsistent findings in bilingual cognitive control reported so far. This explanation is consistent with what was found in the comparative study of multitasking and single task video games (Anguera et al, 2013), and with the supply demand explanation by Schroeder and Marian (2016). Furthermore, the results from the present study lead us to speculate that there might be a development curve of cognitive control enhancement in multitasking training such as L2 training, interpreting training or video games training.…”
Section: Discussionsupporting
confidence: 92%
“…The advantage in the non-linguistic switching tasks yielded by interpreting instead of translation experiences at an early stage of interpreting experience suggests that high-processing demands may be critical to improving cognitive control, which may be able to explain the inconsistent findings in bilingual cognitive control reported so far. This explanation is consistent with what was found in the comparative study of multitasking and single task video games (Anguera et al, 2013), and with the supply demand explanation by Schroeder and Marian (2016). Furthermore, the results from the present study lead us to speculate that there might be a development curve of cognitive control enhancement in multitasking training such as L2 training, interpreting training or video games training.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our hypothesis, yet contrary to previous research by [ 20 , 21 , 62 ], the regression models in Table 6 demonstrated that a traditional knowledge-based operationalisation of multilingualism (as number of languages, early vs. late onset of acquisition, language proficiency and type of language combinations) does not unequivocally lead to enhanced cognitive performance. As individuals differ on many levels, finding an effect of number of languages or degree of cognitive performance would have been strong evidence in favour of a general bilingual advantage.…”
Section: Discussionsupporting
confidence: 71%
“…First, typologically different languages might be more demanding to learn because they share few linguistic commonalities. It has recently been proposed that tasks that are more cognitively engaging will yield greater cognitive benefits (e.g., photographic training is superior to watching documentaries; Park et al, 2014 ), and for language learners, the benefits may be greatest when demands exceed their available cognitive resources ( Schroeder and Marian, 2016 ). Second, typologically similar languages could lead to rapid learning because they share linguistic commonalities (and cognates), leading, after attainment of some proficiency, to competition between the languages exceeding that between distant languages ( Weber and Cutler, 2004 ; Broersma and Cutler, 2011 ; Cutler, 2015 ).…”
Section: The Role Of Language Typologymentioning
confidence: 99%
“…However, younger trilingual adults and children showed the same advantages as bilinguals on inhibitory control measures. Trilingual infants and toddlers performed worse than bilinguals on memory generalization tasks ( Schroeder and Marian, 2016 ). In sum, it is not clear if multilingualism brings about greater cognitive benefits than bilingualism, although the present evidence suggests that it is likely to emerge under certain circumstances.…”
Section: The Cognitive Benefits Of Additional Language Learning: Bilimentioning
confidence: 99%